The Interface Between Loss and Damage, Vulnerability and Human Rights in Africa. - Kabaseke, Charlotte; Odaghara, Chidinma Therese; Ashukem, Jean-Claude N. (Kabale University, 2024)
This article assesses the intersectionality between vulnerability and impact that arise from losses and damages during climate change, in order to highlight the impact that climate change has on human rights in the context of loss and damage in Africa. It further interrogates the adequacy of climate change law in providing solutions to losses and damages and proposes the application of a human rights-based approach as the solution. The article concludes with possible recommendations on how best to improve ways of ensuring that human rights are placed at the centre of seeking solutions to climate change induced losses and damages.